POSTHUMANISM PERSPECTIVE ON ONLINE PARAPHRASING TOOL IN ACADEMIC WRITING WORKS - Ulfah, Badriyah (ENGLISH, 2024)
A substantial portion of the post-humanist argument centers on the ways the domain of convergent technologies transcends, improves, and prolongs life through a range of mind and body enhancements. English lecturers, for example, inadvertently involve technology application assistance in the production of their research articles. Therefore, this study aims (1) to investigate the EFL lecturers’ beliefs toward the use of paraphrasing tools for publishing their research article based on Gladden (2016) framework of Posthumanism, and (2) to find out how they see the impact of paraphrasing tools on their students’ academic writing and intellectual creativity on the writing through a posthumanism lens. 23 EFL lecturers who have experience publishing academic papers and also part of faculty members in their affiliation university would be given a questionnaire consisted opened and closed ended questions for data collection. The data was analyzed and presented qualitatively. The results indicate that the lecturers’ views were containing the analytic and synthetic typology of posthumanism and the use of paraphrasing tools can have both positive and negative impacts on academic writing and intellectual creativity. Hence, the lecturers suggest that students should be taught about the ethics and boundaries of using paraphrasing tools and should be encouraged to develop their own ideas